Predictive genetic testing in children and adults: a study of emotional impact. Issue 8 (1st August 2001) - Michie, S; Bobrow, M; Marteau, T M
Abstract : AIM: To determine whether, following predictive genetic testing for familial adenomatous polyposis (FAP), children or adults receiving positive results experience clinically significant levels of anxiety or depression, and whether children receiving positive results experience higher levels of anxiety or depression than adults receiving positive results. DESIGN: Two studies, one cross sectional and one prospective. SAMPLE: 208 unaffected subjects (148 adults and 60 children) at risk for FAP who have undergone genetic testing since 1990. MAIN MEASURES: Dependent variables: anxiety, depression; independent variables: test results, demographic measures, psychological resources (optimism, self-esteem). RESULTS: Study 1. In children receiving positive results, mean scores for anxiety and depression were within the normal range. There was a trend for children receiving positive results to be more anxious and depressed than those receiving negative results. In adults, mean scores for anxiety were within the normal range for those receiving negative results, but were in the clinical range for those receiving positive results, with 43% (95% CI 23-65) of the latter having scores in this range. Regardless of test result, adults were more likely to be clinically anxious if they were low in optimism or self-esteem. Children receiving positive or negative results did not experience greater anxiety or depression than adults. Study 2. For children receiving a positive test result, mean scores for anxiety, depression, and self-esteem were unchanged over the year following the result, while mean anxiety scores decreased and self-esteem increased after receipt of a negative test result over the same period of time. CONCLUSION: Children, as a group, did not show clinically significant distress over the first year following predictive genetic testing. Adults were more likely to be clinically anxious if they received a positive result or were low in optimism or self-esteem, with interacting effects. The association between anxiety, self-esteem, and optimism suggests that counselling should be targeted, not only at those with positive test results, but also at those low in psychological resources.